2021
DOI: 10.1002/csc2.20486
|View full text |Cite
|
Sign up to set email alerts
|

Performance of novel sorghum germplasm in Pennsylvania and their response to anthracnose

Abstract: Sorghum (Sorghum bicolor L.) has the potential to become a widespread commercial feedstock crop in Pennsylvania, either in rotation with maize (Zea mays L.) or grown alongside it. In other locations where sorghum has been grown for a long time, it is attacked by Colletotrichum sublineola Henn. ex Sacc. & Trotter, a fungal pathogen that causes anthracnose (Colletotrichum sublineola) leaf blight (ALB), thereby diminishing yield. Field surveys were carried out in 2011, 2012, and 2016 to monitor the presence of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The results confirmed that anthracnose resistance response depend on the C. sublineola population present at each location. Multiple studies have shown that anthracnose resistance responses observed in the greenhouse failed under field conditions 28 , 31 , 33 . Small changes in the environmental conditions in the field can favor a greater anthracnose disease pressure to which the plant can respond through a combination of pathogen recognition, activation of the plant immune system and activation of specific metabolic pathways that lead to the production of defense compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed that anthracnose resistance response depend on the C. sublineola population present at each location. Multiple studies have shown that anthracnose resistance responses observed in the greenhouse failed under field conditions 28 , 31 , 33 . Small changes in the environmental conditions in the field can favor a greater anthracnose disease pressure to which the plant can respond through a combination of pathogen recognition, activation of the plant immune system and activation of specific metabolic pathways that lead to the production of defense compounds.…”
Section: Discussionmentioning
confidence: 99%